A DISCOURSE ON DIFFERENCES AND SIMILARITIES BETWEEN THE QUR’ĀN AND THE BIBLE - Suraju, Suraju; Badmus, Saheed (UIN Ar-Raniry, 2017)
The guidance of Allah for mankind is contained in the scriptures se t down by Him through the Prophets and Messengers. These scriptures are numerous due to the number of the Prophets. But, the mentioned and prominent ones include Zabur which was given to Prophet DÃ„ÂwÃ…Â«d, Suhuf which was given to Prophet Ibrahim, TawrÃ„Âh which was given to Prophet Musa, Injil which was given to Prophet IsÃ„Â and the Qur'Ã„Ân which was given to Prophet Muhammad. However, the most circulated ones in the contemporary world are the QurÃ¢â‚¬â„¢Ã„Ân and Bible. These two contain direct and indirect information about different issues and concepts. In spite of the similarities in few areas, the points of divergence are substantial. Hence this paper is aimed at examining five out the areas of convergence as well as the areas of divergence of both the QurÃ¢â‚¬â„¢Ã„Ân and Bible with empirical examples from both scriptures. Conclusion is made to juxtapose their similarities which are due to their divine qualities and their differences which are as a result of the abrogation and interpolation by the people. Thus, the people are encouraged to show due respect to these heavenly scriptures.